Guyana poverty reduction strategy paper ([Office of the President] [Georgetown]GY, 2001)
Provides an analysis of poverty and focuses on public participation. Presents a program designed to reduce poverty over the medium-term. Addresses the macroeconomic framework and budgetary implications of the poverty programme. Deals with the key issues of programme implementation, monitoring and coordination. Outlines the roles of government and civil society.
Keywords: POVERTY ALLEVIATION